Imaging Characteristics of Dacryocystocele Diagnosed after Surgery for Sinonasal Cancer - Debnam, J.M.; Esmaeli, B.; Ginsberg, L.E. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: A dacryocystocele forms when tears accumulate within the lacrimal sac as a result of an obstruction more distally in the lacrimal drainage apparatus, which may occur as a complication of sinonasal surgery. The purpose of this study was to define the imaging characteristics of a postoperative dacryocystocele occurring after surgery for sinonasal cancer and to review the anatomy of the nasolacrimal drainage apparatus.MATERIALS AND METHODS: We reviewed the clinical records and imaging findings of 8 patients who underwent surgery for sinonasal cancer and were diagnosed with a postoperative dacryocystocele between August 2001 and November 2005. The imaging studies performed at the time of diagnosis of dacryocystocele were CT in 6 patients and MR imaging in 2 patients.RESULTS: On both CT and MR imaging, dacryocystoceles had a characteristic appearance of a fluid collection with thin rim enhancement along the course of the affected nasolacrimal duct, with no adjacent solid components. In none of the patients was the dacryocystocele confused with a recurrent tumor.CONCLUSION: Dacryocystocele after surgery for sinonasal cancer has a characteristic appearance on CT and MR imaging. Familiarity with this complication of sinonasal surgery and its appearance on imaging will enable radiologists to avoid misinterpreting dacryocystocele as a recurrent tumor or another process.